Maternal and Child Health Distribution Patterns in Kabupaten Boalemo Provinsi Gorontalo, Indonesia - Bulan Sari; Intan Wahid Ingrat (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Maternal and Child Health (MCH) programs are essential public health efforts aimed at reducing mortality and disease risks among mothers and children. In Gorontalo Province, these programs focus on lowering the maternal mortality rate (MMR) and infant mortality rate (IMR), which remain public health concerns despite progress toward national targets in 2024. Although Gorontalo has achieved the national benchmarks for MMR and IMR, persistent disparities indicate that underlying challenges remain. Cultural practices, educational attainment, poverty, and gender inequality are critical factors that must be considered when evaluating the effectiveness and limitations of existing maternal and child health interventions. Objective: This study aims to describe the distribution of maternal and infant mortality rates in Boalemo Regency, Gorontalo Province, during the period 2018–2021, based on secondary data obtained from the Boalemo Regency Health Profile. Method: A quantitative descriptive approach was employed using secondary data sourced from the Boalemo Regency Health Profile. The data analyzed included annual records of maternal and infant deaths. Data analysis was conducted by organizing the information into tables and graphical displays, followed by narrative interpretation to identify trends and patterns. Results: The findings indicate fluctuations in both maternal and infant mortality rates between 2018 and 2021. Infant mortality rates declined in certain years, whereas maternal mortality rates remained relatively stable but at persistently high levels. These patterns are associated with socio-cultural factors, levels of education, poverty, and gender inequality. Conclusion: The distribution of maternal and infant mortality in Boalemo Regency reveals ongoing challenges in health service delivery. Increasing maternal mortality and fluctuating infant mortality reflect instability in community welfare. A 20.1% gap in antenatal care coverage (K1 and K4 visits) suggests that many pregnant women do not receive adequate care, increasing the risk of complications. Geographical barriers further limit access to health services, underscoring the need for targeted and effective interventions to reduce mortality and improve population health outcomes.